The Influenceof Sharia Financial Technology on the Development of MSMEs - Hutagalung, Muhammad Wandisyah R; Alfadri, Ferri; Nasution, Eswin (Wealth: Journal of Islamic Banking and Finance, 2023)
Currently, the use of fintech is very common in everyday life and continues to increase, but there are still many MSME players who have not been able to realize and be able to use it properly. Increasing financial literacy and the use of fintech can be a big model to help MSME players minimize the risks that occur in making decisions to improve financial performance. The purpose of this study is to determine and analyze the influenceof Fintech Peer to Peer Lending and Payment Gateway on the development of MSMEs in North Sumatra Province. This type of research is field research with a Quantitative approach with primary data obtained from questionnaires that have been distributed to MSME actors in North Sumatra Province, totaling 109 samples which are then processed with Structural Equation Modeling (SEM) techniques.Judging from the results of structural model analysis or inner model throughhypothesis testing path coefficients and T statistical significance values by determining T-statistical values through bootstrapping procedures. So it can be concluded that X1 or P2P has a positive and significant effect on the development of MSMEs in North Sumatra Province. While the resulting value in the variableX2 to Y with t Statistic 2.131 and p Value 0.034 can be explained by the value of t Statistic 2.131 > t table 1.96 or p Value 0.034 < 0.05, then statistically H2 is accepted meaning that variable X2 has a significant effect on Y. So it can be concluded that X2 or Payment Gateway has a positive and significant effect on the development of MSMEs in North Sumatra Province. variabel X2 berpengaruh signifikan terhadap Y. So it can be concluded that X2 or Payment Gateway has a positive and significant effect on the development of MSMEs in North Sumatra Province.